RECURRENT CORRELATIONS OF THE SECOND ORDER BUT SOME THEIR PROPERTIES - Федак, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Considered properties of recurrent correlations of the second order, that are the analogues of equality of Cassini. Reasonable properties of such sequences, related to divisibility of their elements or sums. The set is needed and sufficient terms of divisibility of sum of arbitrary successive m members of sequence Fibonacci on m .